Engaging with climate change : psychoanalytic and interdisciplinary perspectives - Weintrobe, Sally (New library of psychoanalysis., 2013)
How can we help and support people to face climate change? Engaging with Climate Change is one of the first books to explore in depth what climate change actually means to people. It brings members of a wide range of different disciplines in the social sciences together in discussion and to introduce a psychoanalytic perspective. The important insights that result have real implications for policy, particularly with regard to how to relate to people when discussing the issue. Topics covered include: What lies beneath the current widespread denial of climate change; How do we manage our feelings about climate change; Our great difficulty in acknowledging our true dependence on nature; Our conflicting identifications; The effects of living within cultures that have perverse aspects; The need to mourn before we can engage in a positive way with the new conditions we find ourselves inches Through understanding these issues and adopting policies that recognise their implications humanity can hope to develop a response to climate change of the nature and scale necessary. Aimed at the general reader as well as psychoanalysts, psychotherapists and climate scientists, this book will deepen our understanding of the human response to climate change.--